Facial Construction of Hydroxyl Functional Modified Ultrafine BiPO4 with Variation of Dipole Moment Induced by –OH Group - Zhuang Yang; Zengshou Qiang; Jian Wang; Yajun Wang; Wenqing Yao (Small Structures, 2024)
The hydroxyl groups generated by hydrolysis are grafted onto the surface of BiPO4, and a stable surface hydroxylation structure is formed during the subsequent calcination process. This would facilitate the formation of a new hydroxyl functional structure on the surface of the parent photocatalyst without damaging its intrinsic structure. Synchronous illumination X‐Ray photoelectron spectroscopy shows that the hydroxyl functional ultrafine BiPO4 can realize the conversion of defective oxygen to lattice oxygen, which is more conducive in improving the photocatalytic efficiency. The process of filling hydroxyl oxygen vacancies and forming a stable structure is explored using in‐ situ infrared spectroscopy. The induced dipole moment promotes the separation of photogenerated electron–hole pairs, which is beneficial for the enhancement of photocatalytic activity. The dipole moment of the hydroxyl functional‐modified ultrafine BiPO4 is −1.409 D compared to −1.385 D for ordinary BiPO4. The results of this study indicate that hydroxyl functional structure and reduced sample granularity are effective strategies to improve the photocatalytic performance of BiPO4.